Dual-band microstrip loop antenna for wireless application - Ali Saad, Ahmad Mabrook (2013)
In recent years, microstrip and printed antennas are widely used in order to fulfill the commercial needs. The emergence of wireless applications requires compact antenna easy manufacture. The purpose of this project is to design of dual band microstrip loop antenna for wireless applications with a reduction in size. The aim of this antenna was to operate from 2 GHz to 4 GHz. A square microstrip patch antenna has been chosen as antenna design pattern due to its low-profile structure. The development of this project comprised two main stages where the first level is a software simulation (CST Microwave studio2012) and secondly is a hardware development. CST Microwave studio2012 has been used to simulate the antenna design for a purpose of preliminary design which the inherent of the advantages of the antenna can be identified, then the second stage is the development of the microstrip patch antenna which have been fabricated on FR4 substrate and tested using the network analyzer which has range between to 1GHz to 14GHz. Based on this project, the antenna parameters such as return loss, radiation pattern, voltage standing wave ratio (VSWR) and bandwidth have been investigated. For further investigation, a substrate material with higher dielectric constant can be used to reduce a microstrip antenna size. The dual band antenna performance shows agreement between both simulation and measurement results.